(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: The article examines the main aspects of the influence of education on the economic development of Uzbekistan, including the role of educational services in the formation of a qualified workforce, improving the country’s competitiveness and raising the standard of living of the population. Particular attention is paid to the strategic initiatives of the Government of Uzbekistan in the field of education reform, such as the introduction of new educational standards, the development of the private sector in the field of education, as well as the introduction of information technology in the educational process.